Pengaruh Pemasangan Poster Anjuran Buang Sampah terhadap Pemanfaatan Tempat Sampah di Tempat Wisata - Nining Prastiwi; Zahroh Shaluhiyah; Farid Agushybana (Jurnal Promosi Kesehatan Indonesia, 2019)
Background: Cleanliness of tourist area is managers and visitors responsibilities to maintain the beauty of tourist destinations. Disposing of trash in its place becomes very important in maintaining the cleanliness of tourist sites. The role of health promotion media to improve awareness and behavior of tourist in maintaining cleanliness is necessary to be conducted. The purpose of this study was to analyze the effect of providing garbage disposal posters towards the utilising trash bin in tourist sites.Method: This study employs a quantitative method with a quasy experimental approach, non randomized control group pretest posttest design. It was carried out in four tourist sites which consist of two tourist sites as intervention area and the others as control. Sample of this study was consisted of 15 bins/each site which met the criteria of sanitation standards and selected purposively so that the total sample was 30 bins in the intervention and 30 bins in the control areas. The variables included the volume of waste in each trash bin, the quality of trash bin distributed and the number of visitors before and after intervention. Measurements were conducted for 14 days.Results: The volume of waste was increased significantly after providing posters in the intervention sites compared to controls’. Likewise, the quality of trash bin distributed at tourist sites was also increased significantly in the intervention areas compared to controls. The number of visitors at four destinations was increased significantly after intervention because post-test was conducted at long vacation period. That would directly effect to waste volume in the trash bin at 4 tourist destinations. This study recommends to managers to put interesting poster or other instagramable media to promote healthy behaviour related to the cleanliness and beauty at tourist areas.